Ecophysiological and ultrastructural characterisation of the circumpolar orange snow alga Sanguina aurantia compared to the cosmopolitan red snow alga Sanguina nivaloides (Chlorophyta) - Procházková, Lenka; Remias, Daniel; Holzinger, Andreas; Řezanka, Tomáš; Nedbalová, Linda (Polar biology, 2021)
UNLABELLED: Red snow caused by spherical cysts can be found worldwide, while an orange snow phenomenon caused by spherical cells is restricted to (Sub-)Arctic climates. Both bloom types, occurring in the same localities at Svalbard, were compared ecophysiologically. Using a combination of molecular markers and light- and transmission electron microscopy, cells were identified as Sanguina nivaloides and Sanguina aurantia (Chlorophyceae). In search for reasons for a cosmopolitan vs. a more restricted distribution of these microbes, significant differences in fatty acid and pigment profiles of field samples were found. S. aurantia accumulated much lower levels of polyunsaturated fatty acids (21% vs. 48% of total fatty acids) and exhibited lower astaxanthin-to-chlorophyll-a ratio (2-8 vs. 12-18). These compounds play an important role in adaptation to extreme conditions at the snow surface and within snow drifts. Accordingly, the performance of photosystem II showed that one third to nearly half of the photosynthetic active irradiation was sufficient in S. aurantia, compared to S. nivaloides, to become light saturated. Furthermore, formation of plastoglobules observed in S. nivaloides but missing in S. aurantia may contribute to photoprotection. The rapid light curves of the two species show to a certain extent the shade-adapted photosynthesis under the light conditions at Svalbard (high α-value 0.16 vs. 0.11, low saturation point I k 59 vs. 86). These results indicate significant physiological and ultrastructural differences of the two genetically closely related cryoflora species, but the reasons why S. aurantia has not been found at conditions outside (Sub-)Arctic climate types remain unknown. SUPPLEMENTARY INFORMATION: The online version of this article (10.1007/s00300-020-02778-0) contains supplementary material, which is available to authorised users.
Keywords: Arctic; Astaxanthin; Cryoflora; Chlamydomonas nivalis; Polyunsaturated fatty acid; Green algae